Pemahaman Dosen dan Pembelajaran Daring di STAB Dharma Widya - Fernandes, Wira (TIN: Terapan Informatika Nusantara, 2021)
Lecturers as educators are required to be more sensitive to technological developments, but not a few lecturers do not understand the techniques of using and teaching using technology, as a result students feel disadvantaged due to the inability of lecturers to utilize technology, especially during the Covid-19 pandemic. The method used in this research is to use a qualitative approach with descriptive analysis method. Qualitative research is an inquiry strategy that emphasizes the search for meaning, understanding, concepts, characteristics, symptoms, symbols, and descriptions of a phenomenon, is focused and multimethods, natural and holistic, prioritizes quality, uses several ways, and is presented in a narrative. This type of research is field research, which is research conducted by going directly to the field (through online) to explore and research data relating to emotional intelligence. That related to the readiness of Human Resources with teaching during the Covid-19 Pandemic which was carried out online, lecturers understand this condition and try to teach online as well as possible, even though there is limited knowledge in operating these devices, this is not a major obstacle. . The main obstacle for lecturers is the difficulty in knowing the level of understanding of students on the material presented during the class. Regarding the implementation of learning during the pandemic, all lecturers teach online by utilizing available platforms, whether paid or not, this indicates that lecturers understand the importance of continuous learning even during a pandemic period.